Restricted expression of classic cadherins in the spinal cord of the chicken embryo - Lin, Juntang; Wang, Congrui; Redies, Christoph (Frontiers in Neuroanatomy, 2014)
Classic cadherins belong to the family of cadherin genes and play important roles in neurogenesis, neuron migration, and axon growth. In the present study, we compared the expression patterns of 10 classic cadherins (Cdh2, Cdh4, Cdh6, Cdh7, Cdh8, Cdh9, Cdh11, Cdh12, Cdh18, and Cdh20) in the developing chicken spinal cord (SP) by in situ hybridization. Our results indicate that each of the investigated cadherins exhibits a spatially restricted and temporally regulated pattern of expression. At early developmental stages (E2.5–E3), Cdh2 is expressed throughout the neuroepithelial layer. Cdh6 is strongly positive in the roof plate and later also in the floor plate. Cdh7, Cdh11, Cdh12, and Cdh20 are expressed in restricted regions of the basal plate of the SP. At intermediate stages of development (E4–E10), specific expression profiles are observed for all investigated cadherins in the differentiating mantle layer along the dorsoventral, mediolateral, and rostrocaudal dimensions. Expression profiles are especially diverse for Cdh2, Cdh4, Cdh8, Cdh11, and Cdh20 in the dorsal horn, while different pools of motor neurons exhibit signal for Cdh6, Cdh7, Cdh8, Cdh9, Cdh12, and Cdh20 in the ventral horn. Interestingly, subpopulations of cells in the dorsal root ganglion express combinations of different cadherins. In the surrounding tissues, such as the boundary cap cells and the notochord, the cadherins are also expressed differentially. The highly regulated spatiotemporal expression patterns of the classic cadherins indicate that these genes potentially play multiple and diverse roles during the development of the SP and its surrounding tissues.